2003
DOI: 10.1208/ps050106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of disodium ascorbyl phytostanol phosphates (FM-VP4) on cholesterol accumulation within rat intestinal cells

Abstract: ABSTRACTusing liquid scintillation counting in a Beckman LS6500 Scintillation Counter. Dose-response and time course studies were performed in which control (no FM-VP4 treatment) and FM-VP4 (10-100 μM) were co-incubated with 50-μM [ 3 H]cholesterol micelles from 1 minute to 24 hours. Incubation with only 50-μM FM-VP4 for less than 24 hours resulted in a 50% to 60% reduction (n = 6, P < .05) in [ 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…In an in vitro study, DAPP decreased cholesterol accumulation in Caco-2 cells, suggesting that DAPP may modify some extracellular mechanisms of cholesterol influx and efflux (41). Most recently, Wasan et al (42) observed that DAPP reduced the accumulation of cholesterol in cultured rat small intestinal crypt cells and speculated that DAPP might inhibit the interaction of cholesterol or cholesterol micelles with the receptors of enterocytes or act as an antagonist of cholesterol influx channels. Transporters of the ATPbinding cassette (ABC) family appear to play important roles in regulating cholesterol absorption and excretion (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…In an in vitro study, DAPP decreased cholesterol accumulation in Caco-2 cells, suggesting that DAPP may modify some extracellular mechanisms of cholesterol influx and efflux (41). Most recently, Wasan et al (42) observed that DAPP reduced the accumulation of cholesterol in cultured rat small intestinal crypt cells and speculated that DAPP might inhibit the interaction of cholesterol or cholesterol micelles with the receptors of enterocytes or act as an antagonist of cholesterol influx channels. Transporters of the ATPbinding cassette (ABC) family appear to play important roles in regulating cholesterol absorption and excretion (43,44).…”
Section: Discussionmentioning
confidence: 99%
“…Further work by Bhadra and Subbiah showed a significant reduction in cellular cholesterol content with a corresponding increase in sitosterol concentration in human skin fibroblasts and HepG2 cells incubated with liposomes containing sitosterol 26. Recent findings by our laboratory reported that the incubation of Caco‐2 and IEC‐6 cells with FM‐VP4 decreased uptake of cholesterol from the incubation medium 27,28…”
Section: Discussionmentioning
confidence: 75%
“…Phytostanol Phosphoryl Ascorbate (FM‐VP4; Fig. 1) is a water‐soluble phytostanol mixture composed of sitostanol and campestanol ascorbate that has been shown to decrease cholesterol gastrointestinal absorption1–4 and cellular accumulation 27,28. Recent studies from our laboratory have observed that when rats were coadministered FM‐VP4 with radiolabeled and cold cholesterol incorporated into a lipid emulsion (Intralipid ® ), the area under [ 3 H]cholesterol concentration vs. time curve and maximum plasma concentration of [ 3 H]cholesterol were decreased in a dose‐dependent manner 1,2.…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism has been illustrated by an in vitro cholesterol uptake study using cells derived from the duodenal and jejunal segments of rat small intestine (184). In that study, rat intestinal epithelial crypt cells (IEC-6) were incubated with [ (184).…”
Section: Mechanism Of Action Of Disodium Ascorbyl Phytostanyl Phosphatementioning
confidence: 99%